Tubo de calor de água, um estudo teórico-experimental - Cavalcanti, Evandro Sérgio Camelo (1983)
The aim of this work was to develop methodologies for the project, manufacturing and experimental thermal evaluation of heat pipes. The model suggested by SUN and TIEN for theoretical steady-state heat pipe performance was solved for a new condition of cooling fluid and used for predicting the wall temperature profile and saturated vapor temperature. A water heat pipe for a 400 watts heat removal was projected and manufacture. The prototype consists of a copper tube 1.000 mm long, with an outside diameter of 25,4 mm and a wall thickness of 0,79 mm. The wick structure is a composite phosphor bronze wrapped-screen wick with meshes 50 and 250 fitted against the inner wall of the tube to leave a vapor space diameter of 17 mm. The prototype was instrumented and monitored. The measured wall temperature profiles for several heat-input levels are compared and discussed with the theoretical predictions. The methodology for the project of heat pipes was discussed and compared with other procedures suggested by DUNN and CHI.